ISLAM DAN KOMUNIKASI GLOBAL - Suharto Suharto (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2012)
The paper deals with the question of how the Islamic world fcaes the issue of global communication affecting the develpment of religions in the world, especially Islamic tradition in the third countries. The target is the theories of the functions of communication that occur situationally, including those contained in the Quran and the Hadith which give an idea of the values and traditions of communcation in Islam. Ibn Khaldun said that Islam has the concept of tabligh as theory of communication and ethics, since in this concept there are some principles such asonotheism, enjining good and prohibiting evil, Islamic community and piety, while the word (qawl) and writing (qalam) is a timeless tradition in Islamic communication. It is these principles and values that become the basis for Muslim community to determine their position and steps in global community to determine their position and steps in global communitications arena to socialize, mantain and enhance the role of religion (Islam) in the life of mankind.